THE STRUGGLE OF BRIDE AND SWEETNESS AGAINST OPPRESSION IN TONI MORRISON’S GOD HELP THE CHILD - Basri, Maria V V; Wanggai, Febe F I; Kara, Yuliana M D K (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2023)
The aims of the study were to find out the types of oppression experienced by Bride and Sweetness and know the Struggles of Bride and Sweetnees in the God Help the Child. The researcher used the oppression theory by Iris Marion Young to determine the types of oppression experienced by Bride and Sweetness. The research applies African–American literary criticism to analyze woman oppression in Toni Morrison’s God Help the Child. This study used a qualitative descriptive method by looking at Bride and Sweetness struggle againts oppression. This study only focuses on the novel God Help the Child as the object of analysis, and as the subject of analysis focus on the main characters, Bride and Sweetness. The result mentions that there are five types of oppression experienced by Bride and Sweetness in different conditions. The types are exploitation, marginalization, powerlessness, cultural imperialism and violence. Another result is about Bride and Sweetness’s struggle to fight against their oppression. As they experience their own oppression, they have different effort. Bride finally overcomes her trauma and accepts her past, whereas, until the end, people don’t know Sweetness’s blackness since she never revealed it.